Novel phosphonium salts and bifunctional organocatalysts in asymmetric synthesis - Moore, Graham (2013)
This thesis details the syntheses of catalysts and their applications in asymmetric reactions. Initially, the project focused on phase transfer catalysts; quaternary phosphonium salts derived from diethyl tartrate or from commercially available phosphorus compounds and their use primarily in the alkylation of N,N-diphenyl methylene glycine tert-butyl ester. Although some of the salts showed the ability to catalyse the alkylation reaction, all products obtained were racemic. The project then focused on bifunctional organocatalysis; catalysts derived from isoquinoline and BINOL were studied in Michael addition reactions between ethyl nitropropionate and MVK. Possible evidence for a bifunctional effect was observed, however, all Michael addition products obtained were racemic. Finally, an examination of proline-derived diamines as catalysts for aldol reactions is reported. Reversing the positions of the acid and base moieties of the catalyst results in the formation of the opposite enantiomer of the aldol product. In addition, these proline-derived diamines, along with two catalysts derived from a biarylazepine, were tested in a series of asymmetric reactions, with the best enantioselectivities (up to 90% ee) obtained in the conjugate addition between enones and nitro-containing compounds.